Physical characteristics of players within the Australian Football League participation pathways: a systematic review - Jade A. Z. Haycraft; Stephanie Kovalchik; David B. Pyne; Sam Robertson (SpringerOpen, 2017)
Abstract Background Australian football (AF) players require endurance, strength, speed, and agility to be successful. Tests assessing physical characteristics are commonly used for talent identification; however, their ability to differentiate between players across the Australian Football League's (AFL) participation pathway remains unclear. The objective of this review was to quantify the physical characteristics of male AF players across the AFL participation pathway. Methods A search of databases was undertaken. Studies examining tests of physical performance were included, with 27 meeting the inclusion/exclusion criteria. Study appraisal was conducted using a checklist of selection criteria. Results The 20-m sprint time was the most reported test, followed by vertical jump (VJ), AFL planned agility, and 20-m multi-stage fitness test (MSFT). The fastest times for 20-m sprint were for Elite AFL players (range 2.94-3.13 s), with local-level players the slowest (3.22-4.06 s). State Junior Under (U) 18s (58-66 cm) had higher jumps than senior players, with the lowest jumps reported for Local U10s (mean 31 cm). No elite-level data were reported for the AFL planned agility or 20-m MSFT. AFL planned agility times were only reported for talent pathway levels, with large performance variability evident across all levels (8.17-9.12 s). Only mean 20-m MSFT scores were reported from Local U10s to National Draft Camp (6.10-13.50 shuttles). Conclusions Talent pathway players exhibit similar mean test scores irrespective of the physical test, with the exception of 20-m sprint and VJ. Physical tests can discriminate between local participation level players but are less useful within the AFL talent pathway.